2020
DOI: 10.28945/4650
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Awareness and Embracement of Soft Skills by Learning and Practicing Teamwork

Abstract: Aim/Purpose: This paper presents a study about changes in computer science and software engineering students’ perceptions of their soft skills during their progress through the Computer Science Soft Skills course. Background: Soft skills are often associated with a person’s social, emotional and cognitive capabilities. Soft skills are increasingly sought out and are well recognized by employers alongside standard qualifications. Therefore, high importance is attributed to soft skills in computer science and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The qualitative feedback from the student participants clearly emphasized value from team-based learning assessments as it can help with the development of valuable soft skills in a database management course. Relatedly, recent research has identified an increasing interest for the development of social competence and other "soft skills" for IT professionals so they can effectively and successfully work in professional teams upon graduation (Beard et al, 2008;Figl, 2010;Osmani et al, 2016;Ragonis et al, 2020). In fact, research has suggested technical skills alone are insufficient and students need to work to develop a broad set of soft interpersonal skills, including teamwork and communication, as the most desired skills as well as problem solving, working under pressure, conflict management, and negotiation (Osmani et al, 2016).…”
Section: Implications For Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…The qualitative feedback from the student participants clearly emphasized value from team-based learning assessments as it can help with the development of valuable soft skills in a database management course. Relatedly, recent research has identified an increasing interest for the development of social competence and other "soft skills" for IT professionals so they can effectively and successfully work in professional teams upon graduation (Beard et al, 2008;Figl, 2010;Osmani et al, 2016;Ragonis et al, 2020). In fact, research has suggested technical skills alone are insufficient and students need to work to develop a broad set of soft interpersonal skills, including teamwork and communication, as the most desired skills as well as problem solving, working under pressure, conflict management, and negotiation (Osmani et al, 2016).…”
Section: Implications For Educationmentioning
confidence: 99%
“…At the same time, there have been calls in the information technology (IT) education literature for the development of "soft-skills" as a part of the educational experience so that students can effectively and successfully work in professional teams upon graduation (Beard et al, 2008;Figl, 2010;Osmani et al, 2016;Ragonis et al, 2020). In fact, research has suggested technical skills alone are insufficient and IT students need to work to develop a broad set of soft interpersonal skills including teamwork and communication as the most desired skills for development and growth (Osmani et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A soft skills course can also address changes in computer science and software engineering students' perceptions of their soft skills, as explored by Ragonis et al (2020). Their study employed content analysis to categorize and code students' statements.…”
Section: Introductionmentioning
confidence: 99%
“…Given that engineers work in interdisciplinary domains, developing teamwork and communicative competences are needed to engage productively and considerately in practice (Borrego et al, 2013;Passow & Passow, 2017;Trevelyan, 2010). As we saw earlier, for students to critically reflect on generic competences, developmental knowledge of the constituent parts of a particular competence is needed (Necchi et al, 2020;Ragonis et al, 2020).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Other approaches such as analysis of students' logbooks and reflective writing were also found. A single study stood out by using continued assignments for students to explicitly reflect on their 'soft skills' as the point of departure (Ragonis et al, 2020).…”
Section: What Landscape Of Generic Competences Un-folds By Reviewing ...mentioning
confidence: 99%